2016
DOI: 10.1186/s12889-016-3529-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to HPV immunization among blacks and latinos: a qualitative analysis of caregivers, adolescents, and providers

Abstract: BackgroundDespite recommendations that 11–12-year-olds receive the full three-shot Human papillomavirus (HPV) vaccine series, national HPV immunization coverage rates remain low. Disparities exist, with Blacks and Latinos being less likely than Whites to complete the series. We aimed to identify and compare barriers to HPV immunization perceived by healthcare providers, Black and Latino adolescents, and their caregivers to inform a clinic-based intervention to improve immunization rates.MethodsWe conducted sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 32 publications
(25 reference statements)
9
35
0
Order By: Relevance
“…Furthermore, fathers' representation in these studies was considerably low (from 8.3% to 31.9% of the sample) compared to mothers' representation (from 68.1% to 91.7%) [28]. Of the 11 studies identified, only one was conducted exclusively with Latino fathers [24], whereas the other 10 studies that included both parents, and only two explicitly compared outcomes for fathers and mothers [14][15][16][17][20][21][22][23][24]26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fathers' representation in these studies was considerably low (from 8.3% to 31.9% of the sample) compared to mothers' representation (from 68.1% to 91.7%) [28]. Of the 11 studies identified, only one was conducted exclusively with Latino fathers [24], whereas the other 10 studies that included both parents, and only two explicitly compared outcomes for fathers and mothers [14][15][16][17][20][21][22][23][24]26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasing number of studies conducted to identify knowledge and awareness of HPV and the HPV vaccine among various Latino groups in the US [19][20][21][22][23][24][25][26][27], to date, limited information specific to Central Americans exists. In fact, most of the available literature has considered Latinos as a homogeneous group [21][22][23][24], with limited published research and data specific to Central American immigrant parents living in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, vaccine uptake remains remarkably low [7], and Latinos have suboptimal HPV vaccination rates [10][11][12]. Differences in HPV vaccine completion rates between non-Hispanic Whites and minority, high-risk population groups such as Hispanic adolescent females and males have been documented [12][13][14][15][16][17]. It is estimated that increased vaccination and screening coverage for minority population groups has the potential to substantially decrease HPV incidence and mortality attributable to cervical cancer by approximately 83% [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have been conducted to identify HPV knowledge, HPV awareness, and acceptability of the HPV vaccination among Latino population groups [20][21][22][23][24][25][26], only very limited research is specific to Latino fathers. In general, the extant literature has focused on mothers, with a few studies including both mothers and fathers [20][21][22]. Results of this limited research suggest that fathers are less aware of HPV and its health consequences and have lower HPV vaccine-related knowledge [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…The first, as recommended by a study from Boston, suggests longer vaccination appointments so that health care providers have adequate time to educate parents regarding vaccine efficacy and safety. 30 The second, which was discussed in a study from Washington, DC, proposes presenting the HPV vaccine within the context of other common and historically accepted childhood vaccines; this strategy has been called "bundling," and it allows practitioners to approach the HPV vaccine in "a confident and presumptive way," thereby normalizing its administration. 31 High cost also is an important concern in many LMICs due to the costs associated with both procuring multiple doses of the vaccine and delivering the vaccine to all of the target population.…”
Section: Overcoming Barriersmentioning
confidence: 99%